INVESTING IN TEACHER TRAINING FOR BILINGUAL EDUCATION: ECONOMIC AND SOCIAL RETURNS - Sultanova Shohistaxon Shavkatovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This paper examines the economic and social returns of investing in teacher training for bilingual education. It highlights the role of qualified bilingual educators in improving student achievement, fostering cultural inclusivity, and supporting linguistic diversity. The analysis draws on empirical studies from both developed and developing countries, demonstrating how strategic investment in teacher training enhances educational quality, reduces dropout rates, and promotes long-term economic growth. The paper also addresses the social impacts, such as the preservation of minority languages, strengthening of community cohesion, and empowerment of marginalized groups. By linking teacher preparation to measurable educational and economic outcomes, the study provides evidence-based recommendations for policymakers and educational institutions.